2020
DOI: 10.21203/rs.3.rs-26781/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Prevalence and Risk factors of Infertility in a Mongolian Population

Abstract: Background: Worldwide, the median prevalence of infertility is 9%, but rates in different countries vary from 3.5% to 16.7%. Infertility, which is defined by the World Health Organization (WHO) as the failure to conceive after 12 months of unprotected regular sexual intercourse, is not considered a medical condition but carries a social stigma and can greatly impact a couple’s self-esteem and wellbeing. There are a number of risk factors associated with infertility such as: genetic background, age, socio-econo… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
1
0
0
Order By: Relevance
“…In current study the odd of primary infertility increased by 28 fold among women from rural residence as compared to women from urban residence. This finding is consistent with Negdel et al and Mokhtar et al they reported that Females lived in rural areas were more likely to develop infertility relative to those living in urban areas [24,27]. In contrast to our study the study by purkayesta and Abdullah shows urban women are more prone to experience infertility in some regions, which might be due to the differentials in environment and lifestyles.…”
Section: Discussionsupporting
confidence: 91%
“…In current study the odd of primary infertility increased by 28 fold among women from rural residence as compared to women from urban residence. This finding is consistent with Negdel et al and Mokhtar et al they reported that Females lived in rural areas were more likely to develop infertility relative to those living in urban areas [24,27]. In contrast to our study the study by purkayesta and Abdullah shows urban women are more prone to experience infertility in some regions, which might be due to the differentials in environment and lifestyles.…”
Section: Discussionsupporting
confidence: 91%